Single‐breath clinical imaging of hyperpolarized 129xe in the airspaces, barrier, and red blood cells using an interleaved 3D radial 1‐point Dixon acquisition. Issue 4 (April 2016) - Kaushik, S. Sivaram; Robertson, Scott H.; Freeman, Matthew S.; He, Mu; Kelly, Kevin T.; Roos, Justus E.; Rackley, Craig R.; Foster, W. Michael; McAdams, H. Page; Driehuys, Bastiaan
Abstract : Purpose: We sought to develop and test a clinically feasible 1‐point Dixon, three‐dimensional (3D) radial acquisition strategy to create isotropic 3D MR images of 129 Xe in the airspaces, barrier, and red blood cells (RBCs) in a single breath. The approach was evaluated in healthy volunteers and subjects with idiopathic pulmonary fibrosis (IPF). Methods: A calibration scan determined the echo time at which 129 Xe in RBCs and barrier were 90° out of phase. At this TE, interleaved dissolved and gas‐phase images were acquired using a 3D radial acquisition and were reconstructed separately using the NUFFT algorithm. The dissolved‐phase image was phase‐shifted to cast RBC and barrier signal into the real and imaginary channels such that the image‐derived RBC:barrier ratio matched that from spectroscopy. The RBC and barrier images were further corrected for regional field inhomogeneity using a phase map created from the gas‐phase 129 Xe image. Results: Healthy volunteers exhibited largely uniform 129 Xe‐barrier and 129 Xe‐RBC images. By contrast, 129 Xe‐RBC images in IPF subjects exhibited significant signal voids. These voids correlated qualitatively with regions of fibrosis visible on CT. Conclusions: This study illustrates the feasibility of acquiring single‐breath, 3D isotropic images of 129 Xe in the airspaces, barrier, and RBCs using a 1‐point Dixon 3D radial acquisition.Magn Reson Med 75:1434–1443, 2016. © 2015 Wiley Periodicals, Inc.